The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.7717/peerj.12821
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical responses of tropical seagrasses (Family: Hydrocharitaceae) under colonization of the macroalgae Ulva reticulata Forsskål

Abstract: Background Coastal land development has deteriorated the habitat and water quality for seagrass growth and causes the proliferation of opportunist macroalgae that can potentially affect them physically and biochemically. The present study investigates the morphological and biochemical responses of seagrass from the Hydrocharitaceae family under the macroalgal bloom of Ulva reticulata, induced by land reclamation activities for constructing artificial islands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…In Malaysia, E. acoroides, T. hemprichii, Halophila ovalis, H. major, and H. spinulosa possessed higher total phenolic and flavonoid contents in the Ulva reticulata-colonized sites than those of the non-colonized sites. Furthermore, sea walls constructed on the coasts of Mactan Island, Philippines, reduced the hydrodynamic forces and water current velocity, resulting in accumulated nutrients in the seagrass beds and favoring the growth of macroalgae as observed in Merambong, Malaysia (Emmclan et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In Malaysia, E. acoroides, T. hemprichii, Halophila ovalis, H. major, and H. spinulosa possessed higher total phenolic and flavonoid contents in the Ulva reticulata-colonized sites than those of the non-colonized sites. Furthermore, sea walls constructed on the coasts of Mactan Island, Philippines, reduced the hydrodynamic forces and water current velocity, resulting in accumulated nutrients in the seagrass beds and favoring the growth of macroalgae as observed in Merambong, Malaysia (Emmclan et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47][48][49][50] Antioxidants are one of the most important factors in reducing radical compounds in the body to reduce cell damage and ultimately prevent the occurrence of several diseases. 51 Several other types of seagrass such as Enhalus acoroides, Halophila ovalis, Halophila major, and Halophila spinulosa contain flavonoids and phenolics which are commonly known as the largest phytochemical molecules and their antioxidant activity is stronger than vitamins C and E. [52][53][54] Chrysoeriol, one type of flavonoid that is usually studied for its antioxidant effects and is often found in seagrass plants, has a significant effect on increased cell viability, reduced ROS formation, and increased occurrence of antioxidant molecules in H 2 O 2 . In addition, this compound has the ability to suppress peroxidation and has lipid interactions with peroxyl radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Although negative interactions dominate the relationships between seagrasses and macroalgae, there are instances in which positive interactions have been also documented (Ceccherelli and Cinelli, 1999;Ceccherelli and Campo, 2002;Irlandi et al, 2004;Hessing-Lewis et al, 2011;Alexandre et al, 2017;Pereda-Briones et al, 2019;Kalokora et al, 2021;Correia et al, 2022a;Emmclan et al, 2022). While most of these studies have shown that seagrasses could benefit from the presence of macroalgae (Ceccherelli and Campo, 2002;Irlandi et al, 2004;Hessing-Lewis et al, 2011;Pereda-Briones et al, 2019;Kalokora et al, 2021;Emmclan et al, 2022), a couple of studies found the opposite, i.e., a benefit primarily toward the macroalgae (Ceccherelli and Cinelli, 1999;Alexandre et al, 2017;Correia et al, 2022a).…”
Section: Evidence Of Seaweed-seagrass Positive and Neutral Interactionsmentioning
confidence: 99%
“…Although negative interactions dominate the relationships between seagrasses and macroalgae, there are instances in which positive interactions have been also documented (Ceccherelli and Cinelli, 1999;Ceccherelli and Campo, 2002;Irlandi et al, 2004;Hessing-Lewis et al, 2011;Alexandre et al, 2017;Pereda-Briones et al, 2019;Kalokora et al, 2021;Correia et al, 2022a;Emmclan et al, 2022). While most of these studies have shown that seagrasses could benefit from the presence of macroalgae (Ceccherelli and Campo, 2002;Irlandi et al, 2004;Hessing-Lewis et al, 2011;Pereda-Briones et al, 2019;Kalokora et al, 2021;Emmclan et al, 2022), a couple of studies found the opposite, i.e., a benefit primarily toward the macroalgae (Ceccherelli and Cinelli, 1999;Alexandre et al, 2017;Correia et al, 2022a). The presence of macroalgae has been causally associated with increased seagrass shoot density (Ceccherelli and Campo, 2002), enhanced growth (Kalokora et al, 2021) positive changes in seagrass morphology (Ceccherelli and Campo, 2002;Emmclan et al, 2022), and added protection from low-tide associated stressors, excessive epiphyte cover, hydrodynamic disturbance, and ocean warming (Irlandi et al, 2004;Hessing-Lewis et al, 2011;Pereda-Briones et al, 2019).…”
Section: Evidence Of Seaweed-seagrass Positive and Neutral Interactionsmentioning
confidence: 99%
See 1 more Smart Citation